2011
DOI: 10.3945/an.111.000455
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk as a Source of Functional Oligosaccharides for Improving Human Health

Abstract: Human milk oligosaccharides are complex sugars that function as selective growth substrates for specific beneficial bacteria in the gastrointestinal system. Bovine milk is a potentially excellent source of commercially viable analogs of these unique molecules. However, bovine milk has a much lower concentration of these oligosaccharides than human milk, and the majority of the molecules are simpler in structure than those found in human milk. Specific structural characteristics of milk-derived oligosaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 59 publications
(84 reference statements)
4
120
0
Order By: Relevance
“…Mass spectrometry-based characterization of the released glycans identified 18 species, including 6 neutral and 12 sialylated moieties (Table 1). Interestingly, four of the compositions contained fucosylated oligosaccharides, and their detection extends the previous identification of fucosylated oligosaccharides within the bovine milk glycome to N-linked glycoproteins (48).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Mass spectrometry-based characterization of the released glycans identified 18 species, including 6 neutral and 12 sialylated moieties (Table 1). Interestingly, four of the compositions contained fucosylated oligosaccharides, and their detection extends the previous identification of fucosylated oligosaccharides within the bovine milk glycome to N-linked glycoproteins (48).…”
Section: Resultsmentioning
confidence: 61%
“…The glycoproteins in milk thus provide an additional energy source for a select group of infant-associated gut bacteria (48). In this work, we demonstrate that the oligosaccharide portions of bovine milk protein glycoconjugates, once released by an endoglycosidase, can serve as selective growth substrates for infant-associated taxa, such as B. infantis.…”
Section: Figmentioning
confidence: 83%
“…The most pertinent bioactive constituents in colostrum are growth factors and antimicrobial factors (12). A study conducted by Zivkovic and Barile has demonstrated that the acidic oligosaccharides of colostrum played an important role in the prevention of adhesion of pathogenic bacteria to the epithelial surface, but they were unable to describe which mechanism was responsible for this effect (27). In our study, a bioactive hexasaccharide component was identified in colostrum which was found to be accountable for regulating the QS system in S. aureus.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggest that milk oligosaccharides can act as a potential pathogen binding agent due to its structural resemblance with the glycoconjugates resting across the surface of the epithelial cells and thereby resist many infectious diseases. HMO has been found to be very efficient to give rise to a wide range of immuno-modulation effects with its capability to interact directly with the intestinal epithelial cells and enteroendocrine cells (Zivkovic and Barile, 2011). However, it is observed very recently that BMO is a potential source to mimic the benefits of HMO to produce immuno-modulatory effects.…”
Section: Prebiotic Effectsmentioning
confidence: 97%
“…According to a study There are many other bioactive roles of the oligosaccharides in milk have been identified; the beneficial functions of the oligosaccharides in humans were summarized as follows: (1) they supply small amounts of energy, approximately 0-3 kcal/g of sugar substitute, (2) they lower the absorption of dissolved glucose by forming a viscous gel in the gut, (3) they are non-cariogenic, (4) they inhibit diarrhea and symptoms of diarrhea, and (5) The structural complexity of HMO limits its applicability in population groups other than breast-fed children (Zivkovic and Barile, 2011). As some bovine milk oligosaccharides are structurally and functionally close to those found in human milk, it is presumable that bovine milk oligosaccharides could be the first choice to mimic the functions of human milk oligosaccharides (Gopal and Gill, 2000;Zivkovic and Barile, 2011). These functions could include prebiotic activity, inhibition of pathogen binding to epithelial cells, effects on immune response, reduction of inflammatory diseases, structural and functional roles in brain formation, and facilitation of mineral absorption.…”
Section: Bioactive Functions Of Oligosaccharides In Milkmentioning
confidence: 99%